PERBANDINGAN RASIO LIKUIDITAS DAN SOLVABILITAS PADA PT. UNILEVER INDONESIA TBK DAN PT. KINO INDONESIA TBK PERIODE 2015-2024 - Dwiyanti, Raras; Puji Muniarty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze and compare the liquidity and solvency ratios of PT Unilever Indonesia Tbk and PT Kino Indonesia Tbk. The research employs a quantitative comparative approach using secondary data obtained from the companies’ financial statements for the period 2015–2024. The data analysis technique applied is financial ratio analysis, specifically the Current Ratio (CR) and Debt to Equity Ratio (DER). The results indicate that PT Kino Indonesia Tbk has a better level of liquidity compared to PT Unilever Indonesia Tbk, while PT Unilever Indonesia Tbk shows a higher level of solvency. This study is expected to serve as a reference for investors in evaluating the financial performance of companies. This study contributes to the literature by providing comparative financial analysis in the consumer goods sector in Indonesia.